PEMETAAN DAERAH RAWAN KEBAKARAN DI KECAMATAN JABIREN RAYA, KABUPATEN PULANG PISAU, KALIMANTAN TENGAH - Nadia Salsabilah; Mochtar Lutfi Rayes; Dony Rachmanadi (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The area of peatland in Indonesia is estimated at around 13.2 million hectares, which about 5.7 million hectares are found in Kalimantan. Peatlands have many functions such as for water conservation, reducing floods, supporting various kinds of biodiversity, and climate control. However, in 2015 there was a decline in the quality of peatlands, which was triggered by fires that scorched 583.833 hectares in Central Kalimantan. If the fires occur continuously, land degradation will increase and the peat ecosystem will be disturbed. Given these adverse effects, it is necessary to protect an area from fires early by providing a map of forest fire hazard by utilizing geographic information system using scoring and weighting methods. In the making of the map, a combination of natural factors and human factors that were considered as factors in the occurrence of fires were land cover, peat maturity, village centres, road and river networks as well as the central operational-area which later were analyzed with hotspot data. This research was conducted in one of the sub-districts that are considered to have a high level of vulnerability, which was in Jabiren Raya District, Pulang Pisau Regency, Central Kalimantan. The results showed that most of the study areas had a moderate level of vulnerability with the triggering factors of fire was land cover, peat maturity level, and road network.